Life Cycle Assessment Approach of the Tofu Industry in SSIC Balikpapan City to Support SDGs - Muhamad Nur Ibnu Luthfi Saud; Rina Noor Hayati; Muhammad Ma'arij Harfadli; Dinda Jasmine Hasanah (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
The tofu industry constitutes 76% of the enterprises operating in the Somber Small Industry Center (SSIC) of Balikpapan City. Most producers continue to rely on conventional production methods to minimize operating costs, despite their adverse environmental consequences. This study assessed the environmental impacts of tofu production in SSIC Balikpapan and formulated environmentally sustainable improvement strategies using a life cycle assessment (LCA) approach. A quantitative field-survey design was employed, covering all 56 operating tofu industries. Data were collected through interviews, field observations, and documentation, while inventory data were analyzed using SimaPro software and the ReCiPe 2016 Midpoint (H) method. The assessment applied a gate-to-gate system boundary, encompassing production processes from raw material inputs to finished tofu products over a one-year period. The findings showed that the dominant environmental impact categories were human carcinogenic toxicity at 437,000 pt, freshwater ecotoxicity at 19,500 pt, and marine eutrophication at 7,950 pt, primarily resulting from fuelwood consumption and untreated wastewater discharge. The proposed mitigation strategies included replacing fuelwood with liquefied petroleum gas and processing wastewater into liquid organic fertilizer. Implementation of these strategies reduced human carcinogenic toxicity to 26,800 pt, representing a 93.85% reduction, freshwater ecotoxicity to 18,900 pt, representing a 3.08% reduction, and marine eutrophication to 7,940 pt. These findings demonstrate that LCA can effectively identify environmental hotspots and guide cleaner production strategies in small-scale tofu industries. The study provides practical implications for improving resource efficiency, wastewater management, and energy use while supporting Sustainable Development Goals 6, 7, 12, and 13.